Discovery Learning to Improve English Achievement: A Classroom Action Research to the Seventh Graders of SMPN 1 Kedung Jepara - Saidah, Siti (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2020)
This study aims to describe the Discovery Learning Model (DL) to improve the English achievement. The problem is whether the application of DL can improve the English achievement of the seventh graders of SMPN 1 Kedung Jepara. This research applied classroom action research conducted in two cycles, each of which consisted of four stages: planning, implementing, observing, and reflecting. Participants of this study were 36 students, consisting of 20 (55%) girls and 16 (45%) boys. Indicators of success are set when at least 75% of students achieve mastery learning after the applied DL. Results show (1) the average learning achievement in the first cycle was 7.07 and 8.62 in the second cycle the cycle; (2) the mastery learning in the first cycle was achieved by 19 (52.78%) students, and 17 students or 47.22% of incomplete; and (3) completeness of classical learning in cycle I was 52.78% and 100% in cycle II. This means that the results of the second cycle are better than the first cycle. There is also evidence that students activity in the learning process, both individually and in groups increases substantially. Other findings show that the response of the students towards the implementation of DL was 81.81% that indicates very strong agreement.